Postmortem DTI reveals altered hippocampal connectivity in wild sea lions diagnosed with chronic toxicosis from algal exposure. Issue 2 (11th October 2017) - Cook, Peter F.; Berns, Gregory S.; Colegrove, Kathleen; Johnson, Shawn; Gulland, Frances
Abstract: Hundreds of wild California sea lions ( Zalophus californianus ) exposed to the algal neurotoxin domoic acid are treated in veterinary rehabilitation centers each year. Common chronic effects of toxic exposure in these animals are seizures and hippocampal damage, and they have been proposed as a natural animal model for human epilepsy. Humans with medial temporal lobe epilepsy present with white matter pathology in a number of tracts including the fornix and increased structural connectivity between the hippocampus and thalamus. However, there are no prior data on structural connectivity in sea lion brains, with or without neuropathology. In the present study, we used a novel diffusion tensor imaging technique to obtain high resolution (1mm isotropic) white matter maps in brains obtained opportunistically postmortem from wild sea lions with and without chronic clinical signs of toxic exposure to domoic acid. All animals had received a full veterinary workup and diagnosis prior to euthanasia. We measured hippocampal atrophy morphometrically, and all brains were examined histopathologically. In animals diagnosed with chronic domoic acid toxicosis, the fornix showed signs of altered diffusion properties indicative of pathology; these brains also had increased structural connectivity between hippocampus and thalamus in comparison to brains from animals with no neurological signs. These findings establish further parallels between human medial temporal lobe epilepsy and a naturally occurring condition in wild sea lions and simultaneously advance general knowledge of the deleterious effects of an increasingly common natural toxin. Abstract : Wild California sea lions are frequently exposed to the algal toxin domoic acid, leading to neurological signs, seizures, and hippocampal atrophy. Using opportunistic postmortem diffusion tensor imaging of wild sea lion brains, we show altered diffusion properties in the fornix of animals with a likely history of exposure to domoic acid. These findings extend knowledge of the neurobiological effects of this common natural toxin, and match those observed in humans with medial temporal epilepsy.